Tannic Acid Inhibits Salmonella enterica Serovar Typhimurium Infection by Targeting the Type III Secretion System - Shu, Jingyan; Liu, Hongtao; Liu, Yang; Chen, Xindi; Yu, Yu; Lv, Qianghua; Wang, Jianfeng; Deng, Xuming; Guo, Zhimin; Qiu, Jiazhang (Frontiers in Microbiology, 2022)
Salmonella enterica serovar Typhimurium (S. Typhimurium) is an important zoonotic pathogen that can cause food poisoning and diarrhea in both humans and animals worldwide. The type III secretion system (T3SS) encoded by the Salmonella pathogenicity island (SPI) genes is important for S. Typhimurium invasion and replication in host cells. Due to the increasing problem of antibiotic resistance, antibiotic treatment for clinical Salmonella infection has gradually been limited. Anti-virulence inhibitors are a promising alternative to antibiotics because they do not easily induce bacterial antibiotic resistance. Here, we systematically evaluated the therapeutic effect of tannic acid (TA) on Salmonella-infected mice and elucidated its anti-infection mechanism. TA treatment improved the survival rate of S. Typhimurium-infected mice and alleviated cecum pathological lesions. In addition, TA inhibited the invasion of HeLa cells by S. Typhimurium without affecting their growth. Further studies showed that TA could inhibit the expression of sipA and sipB. This inhibition may be implemented by inhibiting the transcription of key regulatory and structural genes of the T3SS. This study provides an alternative antivirulence strategy for Salmonella infection treatment.